Carbon assimilation in Eucalyptus urophylla grown under high atmospheric CO2 concentrations: A proteomics perspective - Santos, Bruna Marques dos [UNESP]; Balbuena, Tiago Santana [UNESP] (Elsevier B.V., 2017)
Photosynthetic organisms may be drastically affected by the future climate projections of a considerable increase in CO2 concentrations. Growth under a high concentration of CO2 could stimulate carbon assimilation-especially in C3-type plants. We used a proteomics approach to test the hypothesis of an increase in the abundance of the enzymes involved in carbon assimilation in Eucalyptus urophylla plants grown under conditions of high atmospheric CO2. Our strategy allowed the profiling of all Calvin-Benson cycle enzymes and associated protein species. Among the 816 isolated proteins, those involved in carbon fixation were found to be the most abundant ones. An increase in the abundance of six key enzymes out of the eleven core enzymes involved in carbon fixation was detected in plants grown at a high CO2 concentration. Proteome changes were corroborated by the detection of a decrease in the stomatal aperture and in the vascular bundle area in Eucalyptus urophylla plantlets grown in an environment of high atmospheric CO2. Our proteomics approach indicates a positive metabolic response regarding carbon fixation in a CO2-enriched atmosphere. The slight but significant increase in the abundance of the Calvin enzymes suggests that stomatal closure did not prevent an increase in the carbon assimilation rates. Biological significance: The sample enrichment strategy and data analysis used here enabled the identification of all enzymes and most protein isoforms involved in the Calvin-Benson-Bessham cycle in Eucalyptus urophylla. Upon growth in CO2-enriched chambers, Eucalyptus urophylla plantlets responded by reducing the vascular bundle area and stomatal aperture size and by increasing the abundance of six of the eleven core enzymes involved in carbon fixation. Our proteome approach provides an estimate on how a commercially important C3-type plant would respond to an increase in CO2 concentrations. Additionally, confirmation at the protein level of the predicted genes involved in carbon assimilation may be used in plant transformation strategies aiming to increase plant adaptability to climate changes or to increase plant productivity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Carbon fixation; Climate change; Plant-environment interaction; Plant metabolism; Subcellular proteomics